Home country effects of multinational network restructuring in times of deglobalization: Evidence from European MNEs - Bruno Merlevede; Bernhard Michel (National Bank of Belgium, 2024)
This paper documents a trend towards deglobalization in European-based multinational networks for the period 2010-2019. In the second half of the decade, the number of foreign contraction episodes shows an increasing trend, while the number of foreign expansions decreased substantially. Foreign expansions also increasingly resulted in a reduced geographic scope of networks (nearshoring) and a higher concentration of activity in geopolitically aligned host countries (friendshoring). We estimate home-country effects of foreign network restructuring by analyzing the number of domestic affiliates and different outcomes for parents and domestic affiliates. We find no evidence of increased home country activity in the wake of foreign contraction episodes, but foreign expansion yields benefits for the domestic economy both along the domestic extensive and intensive margins. A reduced geographic scope and geopolitical reorientation do not induce systematic differences in the home-country effects neither for expansion nor for contraction episodes.
Keywords: F14; F23; F44; 330; International Organization of Production; Multinational Networks; Restructuring; Home Country Effects; Deglobalization